Slow Rise of Trade Politicisation in the UK and Brexit - García, María (2020)
Since the Brexit referendum, the UK government has deployed a vision of ‘Global Britain’ revolving around trade agreements, yet, this was not a key issue in the referendum. Drawing on politicisation literature, we explore the absence of visible activism around future trade policy, in contrast to moderate activity around the EU-US Transatlantic Trade and Investment Partnership (TTIP). We identify actors in UK TTIP mobilisation and trace their actions post-referendum, revealing politicisation as campaigners participate in channels for attempting to influence future UK trade policy. In the presence of these channels and lack of full clarity on future policy, to date, recourse to visible mobilisation in the public space has not yet occurred. Tracing this dynamic process, intertwining Brexit and trade policy, enables us to understand how politicisation of one process affects another. Crucially, given the context of re-nationalisation of trade policy, it allows us to explore how politicisation is operationalised in the absence of one of the key conditions for politicisation suggested in the literature: the transfer of authority to a more remote level of governance.